Resistance and stability of polymers - Ehrenstein, Gottfried W. 1937-; Pongratz, Sonja, 1969- (Hanser Publishers, 2013)
A polymeric material's resistance to different environmental or processing related influences determines its suitability in any number of applications. Reliable information and performance predictions influence material selection. They take a variety of influences into consideration, among them resin manufacture, compounding, stabilization, processing, part design and end use.